Developing River Tourism in Palangka Raya Municipality Central Kalimantan Province - Nenden Dianawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Developing River Tourism in Palangka Raya Municipality Central Kalimantan Province. Currently river tourism is increasingly developing in various regions in Indonesia aside from maritime. Kalimantan Island as the largest island in Indonesia possess abundant potential including the river and it trigger the Regional Government, especially Palangka Raya Municipality in drafting Regional Regulations on Tourism Strategic Areas (KSP). This guideline however, has not fully functionate as their reference in developing tourism destinations in the Capital City of Central Kalimantan Province. This research aiming to provide practical guidance in developing a tourism destinations in KSP 2 Tumbang Tahai which is the focus of the main river tourism activities, with education and conservation as development theme. Qualitative research methods are conducted to identify the potentials by applying previous research approaches that exert parameters of river tourism resources, tourist activities, quality of riverbanks, as well as facilities and infrastructure. The results of the study revealed the availability of the four parameters in preparing recommendations on physical aspects development including zoning layout. In the future, this research is best continued by reviewing non-physical aspects in sharpening analysis and reconcile recommendations, so that the Regional Government has a set of tools in establishing work plans to improve the quality of river tourism in Palangka Raya, becoming Indonesia's leading tourism icon.